PENGARUH LINGKUNGAN KERJA DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN DI PT. DONGJIN INDONESIA - Rizmi Samsul Rizal; Miftahul Jannah; Cecep Abdul Hakim (LP2M Universitas Bina Bangsa, 2023)
This research was conducted with the aim of determining the Effect of Work Environment and Work Discipline on Employee Performance at PT. Dongjin Indonesia by using saturated sample techniques and stratified random sampling. The framework in this study consists of independent variables such as work environment and work discipline, and dependent variables, namely employee performance. The methods used in this study are quantitative methods and data collection techniques in this study using questionnaires. The primary data in this study was with a total sample of 168, the researcher took only half of the sample results of 84 respondents and all available data were analyzed using SPSS Version 25. The results showed that the R Square value was 0.088 or 9%. And the results of the study based on the t test for the work environment have a value of 3,678 > 1,989 and a significant value of 0.000 < 0.05 which means that the work environment has a significant effect on employee performance, while work discipline has a value of 3,348 > 1,989 and a significant value of 0.001 < 0.05 which means that the work discipline variable has a significant effect on employee performance and the F test result has a value of 3.911 >2.71 and a significant value of 0.003 < 0.05, it can be interpreted that The work environment and work discipline simultaneously have a positive and significant effect on employee performance